2017
DOI: 10.1002/cae.21894
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of moodle e‐tests in blended learning educational environment

Abstract: The paper suggests the implementation of association analysis for improving the process of e‐testing in blended learning environment. The research has been conducted using knowledge tests at the Computer Graphics Moodle Course. In the preprocessing phase, data matrices have been created and prepared for the process of discovering significant relationships and links between students' answers to the questions from preparatory tests and those for testing knowledge, the ways of doing, and achieved results. By impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…These authors concluded that LMSs must integrate tools and plugins; not only simple learning analytics, but also EDM tools that permit the use of supervised learning techniques (prediction) [36][37][38] and unsupervised learning techniques (classification) that provide a user-friendly interface for the teacher, which facilitates their use throughout the course of study. These plugins will help with the detection of at-risk students [41] and the implementation of actions to avoid academic failure and high dropout rates [42]. In line with these conclusions, the studies by Moreira Félix et al [37] and Dimić et al [42] placed special emphasis on the advantages of including a prediction module within the plugins in order to facilitate the academic monitoring of students.…”
Section: Characteristics Of the Learning Management System In The Detection Of The At-risk Studentmentioning
confidence: 89%
See 1 more Smart Citation
“…These authors concluded that LMSs must integrate tools and plugins; not only simple learning analytics, but also EDM tools that permit the use of supervised learning techniques (prediction) [36][37][38] and unsupervised learning techniques (classification) that provide a user-friendly interface for the teacher, which facilitates their use throughout the course of study. These plugins will help with the detection of at-risk students [41] and the implementation of actions to avoid academic failure and high dropout rates [42]. In line with these conclusions, the studies by Moreira Félix et al [37] and Dimić et al [42] placed special emphasis on the advantages of including a prediction module within the plugins in order to facilitate the academic monitoring of students.…”
Section: Characteristics Of the Learning Management System In The Detection Of The At-risk Studentmentioning
confidence: 89%
“…However, he concluded that Excel is not an ideal tool, as the number of rows and columns are a limitation for analysing student data. In turn, the studies by Luna et al [36] proposed the use of a Moodle plugin compatible with specific Educational Data Mining (EDM) techniques: supervised and unsupervised Machine Learning techniques [38][39][40][41][42]. These authors concluded that LMSs must integrate tools and plugins; not only simple learning analytics, but also EDM tools that permit the use of supervised learning techniques (prediction) [36][37][38] and unsupervised learning techniques (classification) that provide a user-friendly interface for the teacher, which facilitates their use throughout the course of study.…”
Section: Characteristics Of the Learning Management System In The Detection Of The At-risk Studentmentioning
confidence: 99%
“…Dimić et al in ref. have applied Apriori and Predictive Apriori algorithms for providing feedback to instructors for improvement in the process of e‐testing. Aleem and Gore in ref.…”
Section: Related Workmentioning
confidence: 99%
“…Dimic et al in ref. have utilized the three data matrices created in ref. to apply Apriori and Predictive Apriori algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…The feedback obtained in refs. are based on the students' response which does not consider the students' confidence while marking the answers.…”
Section: Related Workmentioning
confidence: 99%